Development of a Sociodrama Technique Guide in Group Counseling to Enhance Interpersonal Intelligence - Mustia, Ardilla Indah; Darwin, Muhammad Riza; Pristianti, Nindya Ayu (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This research is a Research and Development (R&D) study using the Borg & Gall development model, consisting of seven stages: initial research and information gathering, planning, product development, main field trials, initial trial revisions, revised field trials, and final product. The product is a guide divided into six parts: Introduction, Sociodrama Techniques, Interpersonal Intelligence, Implementation, Sociodrama Scenarios, and Bibliography. Data were collected through questionnaires assessing feasibility by material and media experts, guidance and counseling teachers, and an interpersonal intelligence scale. The trial involved material and media experts, two teachers for initial trials, and eight teachers for the main field trials. Data analysis used a descriptive quantitative method.Results show that the guide is designed with color illustrations, A5 size, hardcover, and aligns with Gardner’s interpersonal intelligence characteristics. It was evaluated as